Paternal contributions to large-for-gestational-age term babies: findings from a multicenter prospective cohort study. (28th February 2019) - Derraik, J. G. B.; Pasupathy, D.; McCowan, L. M. E.; Poston, L.; Taylor, R. S.; Simpson, N. A. B.; Dekker, G. A.; Myers, J.; Vieira, M. C.; Cutfield, W. S.; Ahlsson, F.
Abstract: We assessed whether paternal demographic, anthropometric and clinical factors influence the risk of an infant being born large-for-gestational-age (LGA). We examined the data on 3659 fathers of term offspring (including 662 LGA infants) born to primiparous women from Screening for Pregnancy Endpoints (SCOPE). LGA was defined as birth weight >90th centile as per INTERGROWTH 21st standards, with reference group being infants ⩽90th centile. Associations between paternal factors and likelihood of an LGA infant were examined using univariable and multivariable models. Men who fathered LGA babies were 180 g heavier at birth ( P <0.001) and were more likely to have been born macrosomic ( P <0.001) than those whose infants were not LGA. Fathers of LGA infants were 2.1 cm taller ( P <0.001), 2.8 kg heavier ( P <0.001) and had similar body mass index (BMI). In multivariable models, increasing paternal birth weight and height were independently associated with greater odds of having an LGA infant, irrespective of maternal factors. One unit increase in paternal BMI was associated with 2.9% greater odds of having an LGA boy but not girl; however, this association disappeared after adjustment for maternal BMI. There were no associations between paternal demographic factors or clinical history and infant LGA. In conclusion, fathers who were heavier at birth and were taller were more likely to have an LGA infant, but maternal BMI had a dominant influence on LGA.